Nivel de riesgo obstétrico en mujeres embarazadas que acuden a un centro de primer nivel de atención - Barragán-Hernández, Olga (Universidad de Sonora, 2019)
Introduction: high levels of maternal mortality present in developing countries make it possible to define maternity at risk as the possibility that a woman or the product of suffering damage, injury or even death during gestation, delivery and puerperium processes. Objective: to identify the obstetric risk level in pregnant women attending prenatal consultation to a fist level care center at Hermosillo, Sonora. Methodology: descriptive, cross-sectional study. Population was integrated by pregnant women attending prenatal consultation during January-March of 2016 period. Sampling was for convenience and the sample was 145 pregnant women. The "Obstetric Risk Classification (CRO)" was used as measuring instrument. Results: 22.1% is 18 years old or less. Women between 19 to 25 are the ones that presented the higher obstetric risk (12.4%), in comparison with the teenagers between 18 and less (4.1%). Conclusions: Frequency and quality of prenatal control allows to make integral assessment of the mother-child binomial, contributing to early detection of factors that complicate pregnancy, delivery and puerperium, and may put at risk their lives.